Seed Quality Maintenance of Organic Corn Under Ambient Conditions: Los Baños, Laguna, Philippines - Lucille Elna Parreño-de Guzman; Daphne Cassandra Hilario Gonzales; Dormita R de Carmen; Alma Katrina Blesilda M Gonzales; Liza Lorena E Eustaquio (Faculty of Agriculture, Universitas Gadjah Mada jointly with PISPI, 2026)
Local research and published literature on the physiological and biochemical qualities after storage of organic seeds are currently lacking. Most of the available studies are from international sources and primarily focus on the health benefits of organic produce and products, as well as on yield and meat quality of livestock fed with organic products. Therefore, this research was conducted from April 2021 to October 2023 to develop a storage protocol for organic corn that is practical and adaptable to the conditions of smallholder farmers. Organic corn seeds were collected from farmers in Batanes, Ifugao, Kalinga, and Mountain Province. After initial quality tests, seeds with moisture content (MC) of 10% and below were stored for nine months under ambient conditions at UPLB. Packaging containers used were glass and plastic bottles with silica gel and drying beads as desiccants. Storage of organic corn seeds inside glass bottles with either drying beads or silica gel, under ambient conditions and MC of 10% and below, can maintain high germination and seedling emergence after nine months of storage. From the initial range of 89-97%, germination remained high at 81-97% after nine months of storage, which was confirmed by the high seedling emergence results. This implies that organic seeds, with MC of 10% and below, can be stored in glass bottles for nine months or more under ambient room conditions. This result is particularly valuable for organic farmers who lack access to cold storage facilities but need to store their seeds for the next planting season.